Multiple organs involved in the pathogenesis of non-alcoholic fatty liver disease - Li, Xiaoyan (Cell Biosci, 2020)
Non-alcoholic fatty liver disease (NAFLD) represents the leading cause of chronic liver disease worldwide and the anticipated health burden is huge. There are limited therapeutic approaches for NAFLD now. It’s imperative to get a better understanding of the disease pathogenesis if new treatments are to be discovered. As the hepatic manifestation of metabolic syndrome, this disease involves complex interactions between different organs and regulatory pathways. It’s increasingly clear that brain, gut and adipose tissue all contribute to NAFLD pathogenesis and development, in view of their roles in energy homeostasis. In the present review, we try to summarize currently available data regarding NAFLD pathogenesis and to lay a particular emphasis on the inter-organ crosstalk evidence.